2ln(-x)+8=16

Simple and best practice solution for 2ln(-x)+8=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(-x)+8=16 equation:


Simplifying
2ln(-1x) + 8 = 16

Remove parenthesis around (-1x)
2ln * -1x + 8 = 16

Reorder the terms for easier multiplication:
2 * -1ln * x + 8 = 16

Multiply 2 * -1
-2ln * x + 8 = 16

Multiply ln * x
-2lnx + 8 = 16

Reorder the terms:
8 + -2lnx = 16

Solving
8 + -2lnx = 16

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -2lnx = 16 + -8

Combine like terms: 8 + -8 = 0
0 + -2lnx = 16 + -8
-2lnx = 16 + -8

Combine like terms: 16 + -8 = 8
-2lnx = 8

Divide each side by '-2nx'.
l = -4n-1x-1

Simplifying
l = -4n-1x-1

See similar equations:

| 2(8+2.5y)=16 | | -42=-36t | | 0-3(0)=6 | | 6t+2=2(3t+1) | | y=7-x/2 | | 3z^2+5z+1=3 | | 2x+x+4x=1715 | | 4x-3-6x+2=0 | | 0.25t+0.833=1.5t+0.67 | | (7-2j)-(7+2j)= | | 6x+8=4x+4-2x | | (y*2)+y=957 | | x+(x-3)=31 | | (x-3)(x-3)=20 | | 79-2x=10x-19 | | -5=z/3 | | 2g-32=-32 | | x-(x-1)=81 | | -6x+11=4x | | -2x/x-1+x+3/x^2-1 | | (y+9)+y=37 | | 6x-2=15-110 | | -16+x=43 | | 2x-5y=14 | | x-(x-1)=41 | | (2x+8)(x+4)=0 | | 27=9+x | | 2m^2-15m-27=0 | | -3m(n-2)=3n-5n+9 | | 6c+5u=-49 | | (x-67)+x=261 | | 3(2x-1)-(2-x)-7x=0 |

Equations solver categories